Mapping Caribbean Histories: Glissant, Walcott, and the Counter-Poetics of Modernity - Mbatha, Thembelani (Department of Historical Studies, 2019)
That the history of modernity is characterised by a narrative blindness, wherein the historical and ontological significance of the Black subject is often unjustly overlooked in favour of a Western historiography, is a point that has and continues to concern the scholar of the Caribbean and Black diaspora. Yet while many attempts have been made to counter this fallacy, only tentative moves have been made toward a fundamental interrogation of not only this historiographic taxonomy, but also its broader relation to the poetics and politics of the Caribbean. Accordingly, the following paper seeks to make an intervention into the historiography and narrativity of modernity by considering this history from the position of the Black Caribbean subject, her phenomenology, and poetics. It is the central assertion herein, further, that if the history of modernity is defined by its neglect (its exclusion) of the Caribbean subject, it is important (as the work of Glissant and Walcott helps show) that in addressing this violent falsity we not only replace the proper subject of modernity into narratives of history, but that we also begin to think anew the very philosophical (conceptual) meaning of history itself. Furthermore, rather than seeing modernity (its histories and practices) as distinct from and antithetical to the histories of slavery and colonialism, this paper emphasises the need to reconstruct this relation on the basis of coextension and comutuality. The ambition here is not merely to create a false equation between slavery and modernity, as it is to highlight that critical continuity obtaining between these two sites. Moreover, this crucial continuity may only be well received if the art of the Caribbean artist – and naturally, that of the broader Black diasporic polity – is conceived of more as a space of counter-hermeneutic and historical revisionism.